Analysis of Defect Reduction in Bone Screw Production Using Six Sigma and TRIZ Methods : Analisis Pengurangan Tingkat Cacat pada Produksi Bone Screw dengan Metode Six Sigma dan Triz - Hartono, Daffa Alifio; Sumiati, Sumiati (Universitas Muhammadiyah Sidoarjo, 2025)
General background: The medical device industry plays a crucial role in healthcare, demanding consistently high-quality standards. Specific background: In orthopedic implant manufacturing, particularly in bone screw production, even minor defects can compromise product integrity and patient safety. Knowledge gap: However, there is limited quantitative analysis integrating quality control and inventive problem-solving methods to reduce defect rates in this domain. Aim: This study aims to evaluate product defect levels and propose systematic improvements to enhance production quality. Results: Using Six Sigma and TRIZ methodologies, defect data from January to December 2024 were analyzed. The average Defects Per Million Opportunities (DPMO) was 19,990.17, corresponding to a sigma level of 3.55. Novelty: Improvement proposals were formulated through TRIZ principles, including pre-process calibration, stricter raw material control, SOP updates, task reassignment evaluations, implementation of work performance assessments, and scheduled machine maintenance. Implications: These findings offer a structured approach to reducing defects in high-precision manufacturing settings, with implications for broader adoption in quality-critical industries. Highlights: Identifies high defect levels in bone screw production. Applies Six Sigma and TRIZ for data-driven improvements. Recommends targeted actions to boost production quality. Keywords: Defect Rate, Product Quality, Six Sigma, TRIZ Method, Medical Manufacturing